The Role of Indonesian Language Learning in Facilitating a Multicultural Classroom at Junior High School - Ramadani, Nurhaliza; Ulfah; Yunidar; Nur'aeni, Ida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze how the role of Indonesian language learning as the main communication tool and unifier in multicultural classes at Junior High School. The type of research used is qualitative research. The method used in this research is descriptive method. The data collection techniques used in this research are: 1) Observation, 2) Interview, and 3) documentation. Data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. Based on the results of research on the role of Indonesian language in Junior High School, researchers see the role of Indonesian language learning in multicultural classes can be seen from how to facilitate cultural interaction through the short story "Dia Berbeda" which has a multicultural context that raises multicultural themes, opening space for students to get to know other cultures through stories and characters. Through short stories that contain conflicts and resolutions related to cultural, religious, or social differences, learners are invited to recognize the importance of accepting and understanding each other which strengthens the sense of tolerance between people. Researchers can conclude that the role of Indonesian language learning in multicultural classes can facilitate intercultural interaction through inclusive expression, foster a sense of tolerance through emotional and reflective experiences of the stories read and increase understanding of multiculturalism by presenting the reality of diversity in a form that is close to the lives of students. Not only by learning works of fiction but all Indonesian language learning plays an important role in the multicultural classroom.